Pretreatment with Sucrose Increases Cryoresistance of Mesenchymal Stromal Cells Cryopreserved on Two- and Three-Dimensional Carriers - Mutsenko, Vitaliy V.; Gryshkov, Aleksandr P.; Rogulska, Olena Yu.; Petrenko, Yuriy A. (Problems of Cryobiology and Cryomedicine, 2016)
Probl Cryobiol Cryomed 2016; 26(2):158.